A theoretical model for effective thermal conductivity of open‐cell‐coated metal foams saturated with fluid/phase change material. (8th June 2022) - Saxena, Vivek; Kothari, Rohit; Kumar, Anuj; Sahu, Santosh K.; Kundalwal, Shailesh I.
Summary: The current research presents geometrical effective thermal conductivity (ETC) models for externally coated open‐cell metal foams (MFs) saturated with fluid/phase change material (PCM) by considering three‐dimensional configuration adopted from the tetrakaidecahedron structure. The three‐dimension (3D) models consider different geometries, such as hexagonal and square, involving different shapes of ligaments (cylindrical, concave triprism) and nodes (cubic, pyramidal) for the analysis. The ETC of MF‐composite increases with the coating thickness, the thermal conductivity of coating material, and infiltrating medium. The percentage enhancement in ETC is found to be significant with the increase in coating thickness compared with the increase in thermal conductivity of coating material and infiltrating medium. In addition, the ETC value increases with the increase in the porosity value, which can be explored at the manufacturing process during the design of thermal management systems (TMS). The present model involving hexagonal geometry with concave triprism ligaments and pyramidal nodes is found to be in excellent agreement with test data for all the infiltration cases with an average deviation of less than 3%. The present study reports the mathematical expressions for ETC as a function of various modeling parameters, which can be useful during the design of the TMS. Abstract : The present study reports 3D theoretical models to estimate the effective thermal conductivity (ETC) of coated metal foams saturated with fluid/phase change material. Various geometry of MFs, different shapes of node and ligament have been investigated. Graphene coated MF demonstrated significant increase in the ETC.